Significantly enhanced high permittivity and negative permittivity in Ag/Al2O3/3D-BaTiO3/epoxy metacomposites with unique hierarchical heterogeneous microstructures. (October 2021) - Han, Mingli; Shi, Zhicheng; Zhang, Wenqiang; Zhang, Kun; Wang, Huanlei; Dastan, Davoud; Fan, Runhua
Highlights: Ag/Al2 O3 /3D-BaTiO3 /epoxy composites with unique hierarchical heterogeneous microstructures are fabricated. Numerous hierarchical equivalent micro-capacitors are formed in the composites, yielding substantially enhanced permittivity. The dielectric performances are highly tailorable via adjusting Ag + /Al 3+ mole ratios. A plasma-like negative permittivity phenomenon is observed. Abstract: High dielectric permittivity materials are widely employed in various electronic devices. To satisfy the ongoing miniaturization of electronic devices, materials with further enhanced dielectric permittivities are strongly desired. In this work, a novel design of epoxy composites based on Ag/Al2 O3 /3D-BaTiO3 foams with hierarchical heterogeneous microstructures are prepared. It is found that, the spatial distribution of the Ag particles can be easily controlled via adjusting the Ag + /Al 3+ mole ratios, yielding highly tailorable dielectric properties. When the Ag + /Al 3+ mole ratios are low, the Ag particles are well isolated by surrounding Al2 O3, yielding the formation of numerous equivalent micro-capacitors and substantially enhanced dielectric permittivity. Moreover, the dielectric permittivities of the composites increase with higher Ag + /Al 3+ mole ratios. Consequently, a high dielectric permittivity of 160 @10 kHz, which is about 35 times that of the epoxy matrix, is achieved in the composite with a Ag + /Al 3+ mole ratio of 1.8. Meanwhile, a low tangent of about 0.062 is maintained. As the Ag + /Al 3+ mole ratio increases, the Ag particles become interconnected, forming Ag networks. Consequently, a plasma-like negative phenomenon which should be attributed to the plasma oscillation of free electrons in the percolative Ag networks, is observed. This work offers an effective route to design polymer composites with tailorable high permittivity and negative permittivity.